Arthur John Byng Wavell: a self-proclaimed modern pilgrim in Makkah and Madinah - Spahic, Omer (Dar al-Wahi Publication, 2023)
Arthur John Byng Wavell (1882-1916), a British military officer, Arabist and a fellow of the Royal Geographical Society, secretly visited Makkah and Madinah as a pilgrim in 1908-9. His undertaking was ground-breaking, in that he arrived in Madinah via the historic Hijaz railway that had just become operational. He was the first non-Muslim to do so. His visit illustrated, and his narrative vividly documented, the onset of modernity in the holy cities. Indeed, what Ludovico di Varthema was for the genesis of the general custom of Western Christians in disguise visiting the holy pilgrimage places, Wavell was for the initiation of the custom’s new phase. Wavell was fully aware of his feat. Hence, the travelogue that resulted from his clandestine visit-cum-pilgrimage he titled “A Modern Pilgrim in Mecca and a Siege in Sanaa”. The author explicitly used the adjective “modern” 24 times in a variety of contexts. Some of the noticeable expressions are “modern times”, “modern civilization”, “modern ideas”, “modern traveller” and “modern Turks”. This book delves into the modernity disposition of Wavell’s travel to Makkah and Madinah, using his above-mentioned travelogue as a primary reference. The discussion will place the author’s experiences, as well as interpretations, of the modernity phenomenon in Makkah and Madinah against the backdrop of modernity as a comprehensive concept and ubiquitous trend. The book will focus on the following themes: modernity and modernism versus tradition; Arthur John Byng Wavell and his pilgrimage trip; Arthur John Byng Wavell’s unprejudiced views on Islam; the Hijaz railway as a symbol of modernity; elements of modernity in Makkah and Madinah; Muslims and the challenge of modernity; Arthur John Byng Wavell’s personal experiences and observations.